“Underground Love”: D. H. Lawrence and “Notes from the Underground” by F. M. Dostoevsky - E. A. Markova (Научный диалог)
The reception of the novel by F. M. Dostoevsky “Notes from the Underground” in the works and correspondence of D. H. Lawrence is analyzed in the article. The novelty of the study is in the fact that the influence of this story on Lawrence’s prose is being studied for the first time. Particular attention is paid to Lawrence’s letters to the translator S. S. Kotelyansky, with whom the English writer shared his impressions of reading the works of Russian classics, especially Dostoevsky, as well as to one of the letters addressed to the writer G. Campbell, which contains the only direct reference to “Notes from the Underground” in Lawrence. This letter reveals an individual interpretation of the story by Lawrence. It is proved that this interpretation turns out to be close to the reading of the Notes by L. Shestov. The question is raised about the existing parallels between the text of Dostoevsky and the novels of D. G. Lawrence (“Women in Love”, “The Lost Girl”, “Rainbow” and “Aaron’s Rod”). The similarity is seen in the peculiar interpretation of the Underground concept by Lawrence. It is shown that the image of the Underground in the works of the English writer (usually expressed by the words “underworld”, “subterranean”) is always somehow connected with the irrational principle and is involved in the formation of Lawrence sensualism.